2013
DOI: 10.2147/ppa.s47628
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for suboptimal antiretroviral therapy adherence in HIV-infected adolescents in Gaborone, Botswana: a pilot cross-sectional study

Abstract: ObjectiveLittle is known about factors associated with suboptimal antiretroviral treatment (ART) adherence among adolescents in Sub-Saharan Africa. Our objective was to determine the level of ART adherence and predictors of non-adherence among human immunodeficiency virus (HIV)-infected adolescents at the Botswana-Baylor Children’s Clinical Centre of Excellence in Gaborone, Botswana.MethodsIn a cross-sectional study, 82 HIV-infected adolescents receiving ART and their caregivers were administered a structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 19 publications
1
27
1
Order By: Relevance
“…Eight studies were conducted in South Africa [ 27 34 ], seven in Uganda [ 35 – 42 ], four in Zambia [ 43 46 ] and four in Kenya [ 47 50 ]. Two studies were completed in each of the following countries: Zimbabwe [ 51 , 52 ], Malawi [ 18 , 53 ], Botswana [ 54 , 55 ] and Ghana [ 56 , 57 ]. One study was conducted in both Uganda and Zimbabwe [ 58 ] and another study was conducted in both Uganda and Kenya [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies were conducted in South Africa [ 27 34 ], seven in Uganda [ 35 – 42 ], four in Zambia [ 43 46 ] and four in Kenya [ 47 50 ]. Two studies were completed in each of the following countries: Zimbabwe [ 51 , 52 ], Malawi [ 18 , 53 ], Botswana [ 54 , 55 ] and Ghana [ 56 , 57 ]. One study was conducted in both Uganda and Zimbabwe [ 58 ] and another study was conducted in both Uganda and Kenya [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study by Nachega et al (2009) indicated that it was undertaken in Southern African countries, but the exact countries in the southern African region were not specified [ 61 ]. Among the 36 included studies 17 were qualitative [ 18 , 27 , 28 , 33 , 34 , 40 , 43 47 , 52 54 , 56 58 ], 12 were quantitative [ 29 , 31 , 35 , 37 , 38 , 41 , 48 , 50 , 55 , 59 61 ], and seven were mixed methods [ 30 , 32 , 36 , 39 , 49 , 51 , 57 ]. Overall, 28 were cross-sectional studies [ 18 , 27 30 , 32 – 36 , 39 41 , 43 54 , 56 , 57 ], six were cohort studies [ 37 , 55 , 58 61 ] and two were randomised controlled trials [ 31 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Poor adherence can lead to viral rebound, disease progression, and drug resistance which can compromise patient clinical outcomes and increase the risk of transmitting resistant strains of HIV to others when adolescents become sexually active [4,[6][7][8]. Unfortunately, adherence to ART among children and adolescents is suboptimal [4,5,9,10]. A recent systematic review and meta-analysis [4] that included over 50 studies globally found that only 62.3% of the adolescent and young adult (AYA) population were classified as adherent to therapy assessed by self-report and plasma viral HIV RNA load (VL) levels (adherence at least 85% on self-report or undetectable blood plasma virus levels).…”
Section: Introductionmentioning
confidence: 99%
“…Having a parent or caregiver present at clinical visits appears to be protective of adherence and treatment outcomes among adolescents (18, 19). Adherence has been inconsistently associated with gender (17, 18, 20, 21) and orphan/caregiver status (2123). Lack of caregiver involvement was incorporated into our definition of a positive PSC as we classified non-completion of the PSC as a positive score.…”
Section: Discussionmentioning
confidence: 99%